Recognizing of artifacts during the analysis of histologic slides: a integrative review (Research, Society and Development, 2021)
The pathologist's work aims to diagnose a disease (pathology) through the analysis of tissue or organ fragments removed by biopsy procedures or surgery. This work is hampered by the frequent appearance of artifacts during the interpretation of histological slides, which can often lead to misdiagnosis of the investigated disease. Thus, an integrative review was carried out, guided by the question “What is there in the literature regarding the formation, interpretation and prevention of the appearance of artifacts?”. Data collection was performed on August 12, 2021, at the Virtual Health Library (LILACS and Medline) and National Center for Biotechnology Information (Pubmed) portals. A total of 26 articles were selected, where it was identified that the origin of artifacts can occur in the most diverse stages during the process of making histological slides. Therefore, it was shown that several are the steps that can lead in incorporating artifacts in the slides, such as: during the collection of the previous ones, tissue correction, preparation of blocks, tissue coloring, storage of the before as well as contamination of the slide during its process of assembly. Thus, facilitating the recognition of artifacts when reading histological slides, avoiding possible diagnostic errors.